A bibliometric and visualization analysis on the association between chronic exposure to fine particulate matter and cancer risk - Luo, Xuman; Yang, Qiuping; Zheng, Daitian; Tian, Huiting; Chen, Lingzhi; Wu, Jinyao; Ji, Zeqi; Chen, Yexi; Li, Zhiyang (Frontiers in Public Health, 2022)
Introduction: As one of the major pollutants in ambient air pollution, fine particulate matter (PM2.5) has attracted public attention. A large body of laboratory and epidemiological research has shown that PM2.5 exposure is harmful to human health. Methods To investigate its association with the commonly observed PM-related cancer, a bibliometric study was performed on related publications from 2012 to 2021 from a macroscopic perspective with the help of the Web of Science database and scientometric software VOSviewer, CiteSpace V, HistCite, and Biblioshiny. Results The results indicated that of the 1,948 enrolled documents, scientific productions increased steadily and peaked in 2020 with 348 publications. The most prolific authors, journals, organizations, and countries were Raaschou-Nielsen O, Science of the Total Environment, the Chinese Academy of Sciences, and China, respectively. The top five keywords in frequency order were “air pollution,” “particulate matter,” “lung cancer,” “exposure,” and “mortality.” Discussion The toxic mechanism of carcinogenicity was explained and is worthy of further investigation. China and the US collaborated most closely, and it is hoped the two countries can strengthen their collaboration to combat air pollution. There is also a need to identify the components of PM2.5 and refine the models to assess the global burden of disease attributed to PM2.5 exposure.